2021
DOI: 10.3390/nano11112832
|View full text |Cite
|
Sign up to set email alerts
|

Shallow Donor Impurity States with Excitonic Contribution in GaAs/AlGaAs and CdTe/CdSe Truncated Conical Quantum Dots under Applied Magnetic Field

Abstract: Using the effective mass approximation in a parabolic two-band model, we studied the effects of the geometrical parameters, on the electron and hole states, in two truncated conical quantum dots: (i) GaAs-(Ga,Al)As in the presence of a shallow donor impurity and under an applied magnetic field and (ii) CdSe–CdTe core–shell type-II quantum dot. For the first system, the impurity position and the applied magnetic field direction were chosen to preserve the system’s azimuthal symmetry. The finite element method o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 56 publications
0
9
0
1
Order By: Relevance
“…Semiconductor nanocrystals (SNCs) such as cadmium selenide (CdSe) quantum dots offer wide applications in the fields of photovoltaics, solar energy harvesting, nanophotonics, imaging, sensing and other fields [ 20 , 21 , 22 , 23 , 24 , 25 ]. Since incident radiation causes excitation of free electrons, metal nanoparticles (MNPs) can generate intense electric fields in their vicinity [ 26 ].…”
Section: Theories and Simulationmentioning
confidence: 99%
“…Semiconductor nanocrystals (SNCs) such as cadmium selenide (CdSe) quantum dots offer wide applications in the fields of photovoltaics, solar energy harvesting, nanophotonics, imaging, sensing and other fields [ 20 , 21 , 22 , 23 , 24 , 25 ]. Since incident radiation causes excitation of free electrons, metal nanoparticles (MNPs) can generate intense electric fields in their vicinity [ 26 ].…”
Section: Theories and Simulationmentioning
confidence: 99%
“…The authors obtained a highest performance in a double-QD layers with the maximum luminous yield of 3.64cd/A. Using the finite element method withing the effective mass approximation, Vinasco et al [33] reported the effects of applied magnetic field of the shallow donor impurity states and excitonic contributions in GaAs/AlGaAs and CdTe/ CdSe truncated conical QDs under applied magnetic field. In order to obtain the Coulomb interaction, the authors used a first order perturbative calculation.…”
Section: Introductionmentioning
confidence: 99%
“…Irregularities in materials are found because of impurities' presence; they become zones of attraction or repulsion and create Coulomb-type interactions due to the impurity and carrier charges. The influence of a shallow donor impurity on the excitonic contribution in GaAs/AlGaAs and CdTe/CdSe truncated cone quantum dots can be found in [21]. Ghanbari et al [22] studied the effects of impurity presence on thermodynamic parameters (heat capacity, free energy, entropy, mean energy, and Gibbs free energy).…”
Section: Introductionmentioning
confidence: 99%